2022
DOI: 10.4269/ajtmh.21-0099
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Decline of Zika Virus IgM Antibodies against the NS1 Protein in Imported Israeli Cases

Abstract: Zika virus (ZIKV) infection during pregnancy may cause severe fetal abnormalities and therefore it is important to diagnose and distinguish between recent and past Zika infection. Serological diagnosis assays detect antibodies against the envelope protein, that suffer from high cross-reactivity. In addition, reports regarding long IgM persistence prevent its use in diagnosis of recent Zika infection. Following the Zika pandemic, a novel ELISA assay based on detection of antibodies against Zika nonstructural 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A study examining the sensitivity and kinetics of ZIKV NS1-based ELISA among travelers with ZIKV infection demonstrated higher IgM sensitivity of 79% in the first month and 68% up to two months post-symptoms onset [ 88 ] suggesting that levels of IgM against the NS1 may be declining much faster than IgM antibodies against the envelope protein. Indeed, while envelope IgM persisted for years after infection [ 91 ], NS1 IgM levels were shown to have a 75% decline by 44 days after symptom onset [ 92 ]. This suggests that measuring IgM against NS1 may be better suited for detecting the acute phase of the disease as it allows distinguishing between recent and past infections.…”
Section: Ns1 In Zika Infectionmentioning
confidence: 99%
“…A study examining the sensitivity and kinetics of ZIKV NS1-based ELISA among travelers with ZIKV infection demonstrated higher IgM sensitivity of 79% in the first month and 68% up to two months post-symptoms onset [ 88 ] suggesting that levels of IgM against the NS1 may be declining much faster than IgM antibodies against the envelope protein. Indeed, while envelope IgM persisted for years after infection [ 91 ], NS1 IgM levels were shown to have a 75% decline by 44 days after symptom onset [ 92 ]. This suggests that measuring IgM against NS1 may be better suited for detecting the acute phase of the disease as it allows distinguishing between recent and past infections.…”
Section: Ns1 In Zika Infectionmentioning
confidence: 99%
“…NS1-based ELISA is better suited for detecting the acute phase of ZIKV infection and allows for differentiation between recent and past infections. The limited cross-reactivity of NS1-based ELISA makes it a useful first-line screening tool for travelers, helping to exclude ZIKV infection in individuals returning from ZIKV-endemic regions . The success of ZIKV NS1-based ELISA has led to the development of DENV NS1-based ELISAs, which may provide better diagnostic capabilities, particularly in areas with co-circulation of DENV and ZIKV.…”
Section: Flavivirus Ns1 As a Diagnostic Markermentioning
confidence: 99%
“…The limited cross-reactivity of NS1-based ELISA makes it a useful first-line screening tool for travelers, helping to exclude ZIKV infection in individuals returning from ZIKV-endemic regions. 284 The success of ZIKV NS1based ELISA has led to the development of DENV NS1-based ELISAs, which may provide better diagnostic capabilities, particularly in areas with co-circulation of DENV and ZIKV. NS1 antigen detection for other flaviviruses is less commonly available, but studies have shown the detection of WNV infection using NS1-based ELISA assays, indicating its potential as a diagnostic marker for WNV infections as well.…”
Section: ■ Flavivirus Ns1 As a Diagnostic Markermentioning
confidence: 99%